1985
DOI: 10.1007/bf02902608
|View full text |Cite
|
Sign up to set email alerts
|

Black Banks: A Survey and Analysis of the Literature

Abstract: The analysis of the role of black banks in black economic development began in the early 1970s. At that time the focus was on the profitability of these institutions. Since then both the number of black banks and the research on their performance have increased significantly. This article reviews the recent literature on black banks in order to provide a conceptual framework for policies that will promote their growth and prosperity. The authors conclude that there is a clear need for future research in every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Research suggests a key facet of MOB socially responsible behaviour is found in high levels of risk (Brimmer, 1971;Cole et al, 1985). That risk falls on the deposit side in terms of highly variable deposits, leading MOBs to hold disproportionately high levels of liquidity (Bates and Bradford, 1980).…”
mentioning
confidence: 99%
“…Research suggests a key facet of MOB socially responsible behaviour is found in high levels of risk (Brimmer, 1971;Cole et al, 1985). That risk falls on the deposit side in terms of highly variable deposits, leading MOBs to hold disproportionately high levels of liquidity (Bates and Bradford, 1980).…”
mentioning
confidence: 99%
“…MDIs have been extensively studied, as researchers attempted to examine various characteristics of these institutions and whether they fulfill the FDIC's stated objectives for their promotion, that is, supporting economic viability and stability of the diverse ethnic communities that they serve (e.g. Black et al , 2003; Brimmer, 1971; Cole, 1985; Dymski et al , 2010; Kashian et al , 2014b; Kashian and Drago, 2016; Kwast and Black, 1983).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…With respect to specific minority groups, African American-owned banks have been the most frequently studied to date (e.g. Brimmer, 1971, 1992; Bates and Bradford, 1980; Cole, 1985; Kashian et al , 2014a). There has been some research related to Native American-owned banks (Buckley and Kashian, 2019; Cyree et al , 2004; Vinje, 1996).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Within the types of minority owned banks identified under Section 308 of FIRREA, African American-owned banks have been the most extensively studied to date (for example, Brimmer 1971;Bates and Bradford 1980;Cole 1985;Brimmer 1992;Kashian et al 2014). A few studies have examined minority-owned banks as a group (for example, Black et al 2003;Dymski et al 2010;Kashian and Drago 2016), or two groups (for example, Dymski and Mohanty 1999).…”
Section: Literature Reviewmentioning
confidence: 99%